A Vehicle Dynamics Model for Driving Simulators - Gómez Fernández, Jorge (My University, 2012)
Driving simulators play an important role in research concerning mainly human factors and the development of new advanced driver assistance systems. Since the human body is a very sensitive “machine”, driving simulator experiences must be as close as possible to reality, in order to conduct simulator experiments that generate accurate results, so they can be extrapolated to real driving situations. One part of the driving simulator that influences the driver perception is the vehicle dynamics model. This is the part of the simulator software that calculates the physics and motion of a real vehicle according to the driver inputs and environmental conditions. In this Master’s thesis, a new vehicle dynamics model with ten degrees of freedom has been developed, using Modelica® as a programming language. The model is specially designed for Real-time applications, mainly driving simulators. The model is intended to calculate the motion of a passenger vehicle when driving in normal conditions, representing real vehicle behaviour in public roads, since this is a common characteristic in many simulator experiments. In addition, the model must also present a realistic and predictable behaviour in some severe driving conditions such as collision avoidance manoeuvres, which can also be of interest when performing simulator experiments. A very important part of this thesis concerns the model validation. In order to ensure that the vehicle dynamics model behaves like a real car would do in the conditions mentioned above; predefined manoeuvres representing these driving conditions have been performed in a test track with a car equipped with data acquisition systems. Moreover, the model has been tuned in an attempt to match the test data when performing the same predefined manoeuvres. The last part of the model validation consisted in a simulator experiment where different skilled drivers compared the new model against an old version, in order to evaluate the behaviour of the new model.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport